Self-Assessment in Teaching Interpreting - Postigo Pinazo, Encarnación (TTR, 2008)
AbstractEvaluating interpreter performance is a controversial issue throughout a professional degree (Riccardi, 2002). The training period is vital for introducing future interpreters to habits of recognizing their strengths and weaknesses, lack of specific knowledge and application of learned skills. Integrating self-assessment into teaching and treating it as essential will have positive effects on learners’ attitudes to self-criticism and on performance. Collaborative approaches and technologies make it easier to work with recorded material and enable teachers and students to exchange materials effectively. We have used evaluation sheets for teaching interpreting to our students. We used them in the first stage of training and had students participate actively in evaluating simulated situations in class. This strategy had a positive effect on student commitment and learning and led to better short term results in their performance.